Furthering media independence mechanisms for Future Internet enablement - Corujo, Daniel (2015)
The utilization of Media Independent Handover (MIH) mechanisms, such as the ones provided by the IEEE802.21 standard, allow the abstraction of control and information querying primitives of different wireless access technologies, using a common interface. This not only simplifies the design of high-level entities interfacing with said technologies, but by providing a transport protocol for that interface, such primitives can be used to extend controlling mechanisms towards remote entities. However, the standard only employs such flexible and abstraction capabilities towards handover optimization and facilitation scenarios. In this paper, we take advantage of the flexible design of the MIH mechanisms, and propose evolutions over their base design, allowing their integration into the areas of Internet Multimedia Optimization and the Internet of Things.